Hacia una pedagogía en la virtualidad: ¿vincularidad en tiempos de pandemia? - Bobadilla, María Julia (2020)
This article intends to carry out an analysis on the impact that the COVID 19 pandemic generated in the development of our daily teaching; the process in full development involved rethinking ourselves as subjects in a context of global, particular and singular uncertainty and of how, under these conditions, to approach our teaching task. This new reality led us to generate actions in relation to teaching-learning, through the technological and virtual supports that we had, without having foreseen it in our educational work process. The abrupt incorporation into social networks, as an instance of support for the training process, has caused the different difficulties that arose to carry out pedagogical continuity to become clear, as well as the difficulties of having the technological resources and minimum means to face the "new challenge". We have certain certainties regarding unequal access to digital technological platforms and devices, which further deepen the precarious material and symbolic conditions that have been occurring for both teachers and students, that is, educational gaps. We will share some pedagogical strategies that we have been developing through social networks to maintain the best possible relationship with students in the field of social work 1 and thus begin the process of responses to the new questions that this particular situation generated for us.